Analisis Kapasitas Sistem Informasi ELSIMIL dalam Mendukung Kebijakan Percepatan Penurunan Stunting di Jawa Timur: - - Abdul Fatah Fanani; Sri Handayani; Ermatry Hariani (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2026)
Stunting remains a complex public health issue in Indonesia, necessitating the support of a reliable information system for data-driven interventions. This study aims to analyze the capacity of the Electronik Siap Nikah dan Hamil (ELSIMIL) information system in supporting policies to accelerate stunting reduction in East Java Province. The study employs a quantitative research method with a descriptive approach involving 2,644 respondents who are ELSIMIL users across multiple administrative levels. Data were collected through a questionnaire based on the Health Metrics Network (HMN) framework, covering the dimensions of resources, indicators, data sources, data management, dissemination, and data quality. The findings indicate that the overall capacity of the ELSIMIL system is moderately adequate, particularly in terms of indicator relevance, data availability, and the utilization of information for decision-making. However, several challenges persist, including disparities in digital infrastructure, variations in user capacity, limited system interoperability, as well as issues related to data quality and timeliness. These findings underscore the need to strengthen governance, enhance human resource capacity, improve system integration, and expand technological infrastructure. Therefore, optimizing ELSIMIL as a data-driven information system is essential to support the effectiveness and sustainability of stunting reduction policies.